Early harvest increases post-harvest physiological quality of Araucaria angustifolia (Araucariaceae) seeds - Shibata, Marilia; Medeiros Coelho, Cileide Maria (Revista de Biología Tropical, 2016)
Araucaria angustifolia is a conifer native to Brazil and is an endangered species. Since this species seeds have a short period of viability, its vulnerability is higher. Thus the aim of this study was to evaluate the physiological quality of A. angustifolia seeds during the development and post-storage periods. For this, cones of A. angustifolia were collected from a natural population in Curitibanos, Santa Catarina, Brazil, in March, April, May, June, and July 2012. The collected seeds were classified into developmental stages of cotyledonary, I, II and III according to the month of collection; a total of 10 cones were collected for each stage. Seeds were stored in a refrigerator for 60 and 120 days, and were submitted to a chamber germination test (25 °C-photoperiod 12 h). Additionally, seeds were tested for moisture content (105 °C for 24 hours), tetrazolium (0.1 % for 1 hour) and vigor (electric conductivity [75 mL distilled water at 25 °C], germination speed index, and shoot and root length). Our results showed that during seed development, moisture content decreased from the cotyledonary stage (66.54 %) to stage III (49.69 %), and vigor increased in the last stage. During storage, moisture content at cotyledonary stage and stage I was stable. On the other hand, stored seeds exhibited a decrease in moisture content after 120 days at stages II and III. Physiological quality at the cotyledonary stage resulted in an increased germination rate of 86 % and 93 % after 60 and 120 days of storage, respectively; unlike stages II and III exhibited a decrease in seed viability and vigor after storage. Electrical conductivity was higher for fresh seeds at the cotyledonary stage, than for those stored for 60 and 120 days. However, in other stages, released leachate content after 120 days of storage, increased with the advance of the collection period. Germination speed index and shoot and root lengths after storage were highest for seeds at the cotyledonary stage and stage I; unlike stages II and III which had short root and shoot lengths during storage. Thus, the maintenance of seed moisture content during storage was variable and dependent on the period of collection. Furthermore, the physiological quality differed among earlier and later stages. Early collection favored seed physiological quality, and may be a strategy for better conservation of A. angustifolia seeds.